1998
DOI: 10.1093/hmg/7.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive Scanning Approach to Screen All the Mitochondrial tRNA Genes for Mutations and Its Application to the Investigation of 35 Independent Patients with Mitochondrial Disorders

Abstract: To gain a better understanding of the molecular basisof mitochondrial (mt) encephalomyopathies, a highly heterogeneous condition, we developed a denaturing gradient gel electrophoresis-based approach that allows rapid and exhaustive screening for mutations of all 22 mt tRNA-encoding genes and their flanking regions in large cohorts of patients. This method, that detects heteroplasmy (i.e. co-existence of mutant and wild-type mtDNA species in various ratios) directly, was applied to the investigation of 35 inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 32 publications
(38 reference statements)
2
43
0
Order By: Relevance
“…Laboratory methods that can be used to screen for known point mutations include PCR with restriction fragment length polymorphism (RFLP) analysis to screen for specific mutations on a single basis or multiplex PCR with allele specific oligonucleotide (ASO) analyis to screen for multiple known mutations simultaneously. Methods that can be used to screen for unknown mtDNA point mutations include single-strand conformation polymorphism (SSCP) [119], heteroduplex screening assays (such as temporal temperature gradient gel electrophoresis (TTGE) [120][121][122], temperature gradient gel electrophoresis (TGGE) [123], denaturant gradient gel electrophoresis (DGGE) [124,125], denaturing high performance liquid chromatography (dHPLC) [126]), and sequencing. As direct DNA sequencing is generally considered to be the gold standard for mutation detection in nuclear genes, the advent of rapid sequencing tools has resulted in some laboratories including mtDNA sequencing in their clinical diagnostic approach by one of several different sequencing methodologies available.…”
Section: Mitochondrial Dna Analysismentioning
confidence: 99%
“…Laboratory methods that can be used to screen for known point mutations include PCR with restriction fragment length polymorphism (RFLP) analysis to screen for specific mutations on a single basis or multiplex PCR with allele specific oligonucleotide (ASO) analyis to screen for multiple known mutations simultaneously. Methods that can be used to screen for unknown mtDNA point mutations include single-strand conformation polymorphism (SSCP) [119], heteroduplex screening assays (such as temporal temperature gradient gel electrophoresis (TTGE) [120][121][122], temperature gradient gel electrophoresis (TGGE) [123], denaturant gradient gel electrophoresis (DGGE) [124,125], denaturing high performance liquid chromatography (dHPLC) [126]), and sequencing. As direct DNA sequencing is generally considered to be the gold standard for mutation detection in nuclear genes, the advent of rapid sequencing tools has resulted in some laboratories including mtDNA sequencing in their clinical diagnostic approach by one of several different sequencing methodologies available.…”
Section: Mitochondrial Dna Analysismentioning
confidence: 99%
“…Diseases commonly associated with mitochondrial DNA (mtDNA) mutations are as follows: myopathy, encephalopathy, lactic acidosis, and stroke-like episodes (MELAS); myoclonus epilepsy, and ragged red fibers (MERRF); neuropathy, ataxia, and retinitis pigmentosa (NARP); Leber's hereditary optic neuropathy (LHON); and Kearns-Sayre syndrome. Single-nucleotide changes are common causes of MELAS (m.3243A4G), MERRF (m.8344A4G), NARP (m.8993T4G/C), and LHON (m.11778G4A), while KearnsSayre syndrome is associated with deletions [Moraes et al, 1989;Sternberg et al, 1998;Wong, 2007]. Variation in mtDNA is described in cancerous lesions and assessment of mtDNA is extensively used in forensic applications [Hatsch et al, 2007;Mithani et al, 2007;Tobe and Linacre, 2008;Wang et al, 2008b;Webb et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Heteroplasmy of A5656G, however, can be an artifact of RFLP analysis (Finnilä et al, 1999). This mutation, previously observed by Thomas et al (1996) was found to be in connection with A12308G (a marker for mtDNA haplogroup U), T3197C (a marker for haplogroup U5), and T5814C (which was associated with mitochondrial encephalopathy; Manfredi et al, 1996) in a patient with limb myopathy (Sternberg et al, 1998). Indeed, it is now well known that a transition at position 5656 (which is located as a non-coding spacer between the tRNA Ala and tRNA Asn genes) is characteristic of a sub-haplogroup (now referred to as U5b1; Tambets et al, 2004) of the European haplogroup U5b (Finnilä et al, 1999(Finnilä et al, , 2001Herrnstadt et al, 2002).…”
mentioning
confidence: 59%